2015
DOI: 10.1002/ajmg.b.32388
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiological basis of human aggression: A review on genetic and epigenetic mechanisms

Abstract: Aggression is an evolutionary conserved behavior present in most species including humans. Inadequate aggression can lead to long-term detrimental personal and societal effects. Here, we differentiate between proactive and reactive forms of aggression and review the genetic determinants of it. Heritability estimates of aggression in general vary between studies due to differing assessment instruments for aggressive behavior (AB) as well as age and gender of study participants. In addition, especially non-share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 252 publications
(287 reference statements)
2
105
0
3
Order By: Relevance
“…1,2 Studies have shown that externalizing behaviors are highly heritable (55–65%). 35 Variation in genes implicated in dopaminergic, serotonergic, and neuroendocrine systems appears to increase risk for development of externalizing behaviors. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Studies have shown that externalizing behaviors are highly heritable (55–65%). 35 Variation in genes implicated in dopaminergic, serotonergic, and neuroendocrine systems appears to increase risk for development of externalizing behaviors. 3 …”
Section: Introductionmentioning
confidence: 99%
“…35 Variation in genes implicated in dopaminergic, serotonergic, and neuroendocrine systems appears to increase risk for development of externalizing behaviors. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, current research aims to identify genetic variants associated with aggressive behaviors, which may help to inform candidate gene selection and the identification of gene pathways to gain further understanding of the genetic substrate of this complex trait [Kudryavtseva et al, 2015;Waltes et al, 2015;Zhang-James and Faraone, 2015]. Gene selection has predominantly been driven by inspecting genes and neurobiological pathways with an established association with aggression, including the serotonin (5-HT) gene, levels of which were found to be low in more aggressive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Our study cannot directly address this question but hypotheses that temperamental characteristics such as anxiety, anger or psychopathic traits [26] could partly explain the common variation at the baseline level of PA and RA is supported by our results. Also, researchers have recently proposed that neurotransmitters from the aminergic system could be involved in the regulation of both PA and RA [44] through their role in response to stress and rewards. We found evidence of common genetic factors associated with developmental changes of PA and RA.…”
Section: Discussionmentioning
confidence: 99%